Interferensi Interlanguage Dalam Penerjemahan Arab–Indonesia: Studi Penyimpangan Linguistik Pada Perguruan Tinggi Agama Islam - Bintang Rosada; Irma Sani Daulay; Nurul Huda Salmas; Novriyani (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Translation has long been associated merely with the process of transferring one language into another without altering the essence of the meaning, with the expectation that the intended message can be conveyed properly. Students tend to position translation activities only at the thematic and ideological level of coursework, and thus have not fully explored how a translation can appear natural and meaningful by paying attention to grammar and sentence flow. Therefore, this study aims to describe translation errors or identify interlanguage phenomena consisting of simplification, generalization, and fossilization through a qualitative approach focusing on Larry Selinker’s theory, case studies, and descriptive assessment. The primary data source of this research is the translation of texts from the book Arabiyah Bayna Yadaik 3A used by fifth-semester students of STAIN Mandailing Natal, supported by secondary data from reputable national and international journals, as well as additional supporting data in the form of documentation and academic interviews. The results of the study indicate that students assume translation is merely the transfer of the source language into the target language. Consequently, the translation results contain more complex interlanguage phenomena, not merely the formation of a unique language between two languages such as abbreviations, but also literal meanings (reduction and shift of meaning), simplification of meaning, word repetition (addition of meaning), contextual errors, grammatical errors, semantic errors, and structural errors. Translation errors or interlanguage found in the translation results of fifth-semester students of the Arabic Language and Literature program in the book Arabiyah Bayna Yadaik Volume 3A are not limited to fossilization alone, where the mother tongue dominates in shaping the translation or creating a new language that becomes the translator’s identity (students), causing the translation to appear unnatural. There is also a tendency among students to simplify translations (simplification) in order to complete assignments more easily for the sole purpose of academic grades, as well as a tendency toward word generalization (generalization), which repeatedly applies a single rule to translate various complex sentences. The study concludes that translation is not merely a process of transferring language so that messages can be conveyed, but rather a series of intellectual and cognitive activities in transferring messages, nuances, meanings, language styles, and cultural aspects from the source